Microtremor Data to Strengthen the Students Mastery of Materials in the Implementation of Integrated Physics Learning - Rohima Wahyu Ningrum; Hendra Fauzi; Wiwit Suryanto; Estuning Tyas Wulan Mei; Risky Nuri Amelia (Universitas Negeri Surabaya, 2020)
A geophysical research has been conducted to determine the level of hazard vulnerability in West Halmahera by using microtremor data. Microtremor data are analyzed using the Horizontal to Vertical Spectral Ratio (HVSR) method and it is processed using Geopsy software to know hazard vulnerability level in the region . Data analysis and processing are used as sources of information in physics learning materials using an integrated learning model. Research objectives are to train the students to understand the materials in the fields of study and to enhance other discovery ideas.This research method uses the correlational method and the type of research is experimental research. The research design is an uniquecase research design and the instrument used is tests and questionnaires. The results of this research indicate that the microtremor data using integrated learning models of integrated types have effect on the students Mastery of materials in the implementation of physics learning. The effect of the integrated learning model of integrated type on the students Mastery of materials on the concepts of vibration and waves is 16% and it is in low category. Whereas, the students' responses to integrated learning model of integrated type are quite fun and it can help to improve their mastery of the material on the concepts of vibration and waves.